Cost Analysis and Treatment of Covid-19 Patients with Comorbidities at Rspad Gatot Soebroto - Petrus Kabul Togarma; Yusi Anggriani; Hesty Utami R; Dewiyana Andari K (Green Publisher Indonesia, 2024)
The COVID-19 pandemic has significantly affected the global health sector, especially in patients with comorbidities such as type-2 diabetes mellitus and hypertension. Patients with these comorbidities require special attention and proper handling during the COVID-19 treatment process, given the higher risk of complications in this group. Gatot Soebroto Army Hospital, as a referral center for COVID-19 in Indonesia, faces the complexity of handling patients who often have complicated clinical conditions which are also related to the costs required. Therefore, analyzing the cost and treatment of COVID-19 patients who also suffer from comorbidities such as hypertension, type-2 diabetes mellitus, type-2 diabetes mellitus and hypertension is essential to improve care management. This study took place from January to July 2021 at Gatot Soebroto Army Hospital. The purpose of the study was to determine the cost and treatment of COVID-19 and the relationship between severity and outcomes. The method used was retrospective observational in COVID-19 patients with these comorbidities. The results showed that the largest cost expenditure came from room and accommodation costs. The highest average total cost came from a combination of comorbid hypertension and type-2 DM. The frequently used treatment profile showed antiviral therapy (favipirapir), antibiotics (Levofloxacin and Azithromycin), anticoagulants (heparin), corticosteroids (dexamethasone), and symptomatic (paracetamol). Improvement in clinical condition was the highest clinical outcome. The result of Chi-Square test analysis between severity and clinical outcome was significant (p-value 0.007<0.05). In conclusion, the treatment profile is adjusted to the clinical condition and the severity of COVID-19 affecting the clinical outcome.